1996
DOI: 10.1103/physrevd.54.7513
|View full text |Cite
|
Sign up to set email alerts
|

Planetoid string solutions in 3+1 axisymmetric spacetimes

Abstract: The string propagation equations in axisymmetric spacetimes are exactly solved by quadratures for a planetoid Ansatz. This is a straight non-oscillating string, radially disposed, which rotates uniformly around the symmetry axis of the spacetime. In Schwarzschild black holes, the string stays outside the horizon pointing towards the origin. In de Sitter spacetime the planetoid rotates around its center. We quantize semiclassically these solutions and analyze the spin/(mass 2 ) (Regge) relation for the planetoi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
166
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(173 citation statements)
references
References 16 publications
5
166
1
1
Order By: Relevance
“…Let us mention that to arrive to the result in the last line in (4.15) we have assumed the prescription in which the sums over n (in infinite limits) are computed before doing the integral over ω so that one is allowed to do shifts of the summation index n. If one would instead assume that the integral over ω (in infinite limits) is done before the evaluation of the sums the result would be different. 1 We shall discuss the origin of this ambiguity in Appendix C. Performing similar shifts of ω and n in the last two lines in (4.11) we get 16) where the final term should be summed over n = 0, 2.…”
Section: Short String Limit Of Folded Spinning String Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us mention that to arrive to the result in the last line in (4.15) we have assumed the prescription in which the sums over n (in infinite limits) are computed before doing the integral over ω so that one is allowed to do shifts of the summation index n. If one would instead assume that the integral over ω (in infinite limits) is done before the evaluation of the sums the result would be different. 1 We shall discuss the origin of this ambiguity in Appendix C. Performing similar shifts of ω and n in the last two lines in (4.11) we get 16) where the final term should be summed over n = 0, 2.…”
Section: Short String Limit Of Folded Spinning String Solutionmentioning
confidence: 99%
“…With this motivation in mind here we revisit the computation of the 1-loop quantum correction to the energy of the prototypical example of rotating string -folded rotating string located at the center of AdS 5 [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In [3] it was suggested that a spinning string state represented by the classical solution for a long rotating string in AdS [13] may be related, in the limit of large spin S, to the minimal twist operators on the gauge theory side. An evidence in favour of this proposal is the scaling of the dimension as ∆ = S + c 1 ln S + .... for large S in the two limits (λ ≫ 1 and λ ≪ 1) of the duality, as well as the absence [14,15] of higher-order (ln S) n corrections on the string side to all orders in the inverse string tension (…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the expected melting of glueballs when their energy approaches the average plasma kinetic energy. In the AdS picture, they correspond to "planetoids" [18,19] orbiting the large AdS black hole that represents the thermal ensemble.…”
Section: Introductionmentioning
confidence: 99%